MPK3 and MPK6 control salicylic acid signaling by up-regulating NLR receptors during pattern- and effector-triggered immunity. (15th January 2022) - Lang, Julien; Genot, Baptiste; Bigeard, Jean; Colcombet, Jean
Abstract : Up-regulation of NLR immune receptor genes is common to pattern- and effector-triggered immunity, relies on similar, albeit differently articulated, signaling components, and promotes the salicylic acid sector of defense. Abstract: Arabidopsis thaliana mitogen-activated protein kinases 3 and 6 (MPK3/6) are activated transiently during pathogen-associated molecular pattern-triggered immunity (PTI) and durably during effector-triggered immunity (ETI). The functional differences between these two kinds of activation kinetics and how they coordinate the two layers of plant immunity remain poorly understood. Here, by suppressor analyses, we demonstrate that ETI-mediating nucleotide-binding domain leucine-rich repeat receptors (NLRs) and the NLR signaling components NDR1 and EDS1 can promote the salicylic acid sector of defense downstream of MPK3 activity. Moreover, we provide evidence that both sustained and transient MPK3/6 activities positively control the expression of several NLR genes, including AT3G04220 and AT4G11170 . We further show that NDR1 and EDS1 contribute to the up-regulation of these two NLRs in both an ETI and a PTI context. Remarkably, whereas in ETI MPK3/6 activities are dependent on NDR1 and EDS1, they are not in PTI, suggesting crucial differences in the two signaling pathways. Finally, we demonstrate that expression of the NLR AT3G04220 is sufficient to induce expression of defense genes from the salicylic acid branch. Overall, this study expands our knowledge of MPK3/6 functions during immunity and provides new insights into the intricate interplay of PTI and ETI.